An Analysis of the Safety of Medication Ordering Using Typo Correction within an Academic Medical System - Darby, Alaina Brooks; Karas, Brittany Lee; Wagner, Tina (Applied Clinical Informatics, 2021)
Objectives Spelling during medication ordering is prone to error, which can contribute to frustration, confusion, and, ultimately, errors. Typo correction can be utilized in an effort to mitigate the effects of misspellings by providing results even when no exact matches can be found. Although, typo correction can be beneficial in some scenarios, safety concerns have been raised when utilizing the functionality for medication ordering. Our primary objective was to analyze the effects of typo correction technology on medication errors within an academic medical system after implementation of the technology. Our secondary objective was to identify and provide additional recommendations to further improve the safety of the functionality.Methods We analyzed 8 months of post-implementation data obtained from staff-reported medication errors and search query information obtained from the electronic health record. The reports were analyzed by two pharmacists in two phases: retrospective identification of errors occurring as a result of typo correction and prospective identification of potential errors with continued use of the functionality.Results In retrospective review of 2,603 reported medication-related errors, 26 were identified as potentially involving typo correction as a contributing factor. Six of these orders invoked typo correction, but none of the errors could be attributed to typo correction. In prospective review, a list of 40 error-prone words and terms were identified to be added as stop words and 407 medication synonyms were identified for removal from their associated medication records.Conclusion Our results indicate, when properly implemented, typo correction does not cause additional medication errors. However, there may be benefit in implementing further precautions for preventing future errors.
Keywords: electronic health record; clinical decision support; medical informatics applications